Redaksi Buana ANALISIS BENTUK PELANGGARAN MAKSIM TUTURAN TOKOH CERPEN HARGA SEORANG PEREMPUAN KARYA OKA RUSMINI SEBAGAI MATERI OTENTIK PEMBENTUKAN KARAKTER (Buana Bastra, 2014)
This study aims to clarify the following two things. First, the violation of the character's politeness speech principle in the short story "Harga Seorang Perempuan" in Oka Rusmini's work. Second, the impoliteness figure in literature as authentic material for character building. The method used was descriptive and qualitative research and data were classified as figures of impoliteness speech acts. The data source of this research was from the speech of the characters in the short story "Harga Seorang Perempuan" (Price of a Woman) in Oka Rusmini's work in the short story collection titled "Sagra". Data were analyzed by identifying figures' utterances that showed Impoliteness language by applying the principles of Leech politeness. The results of this study were ( 1 ) Found violation of character's politeness principle in the short story "Harga Seorang Perempuan" by Oka Rusmini, which was seen in the two figures, namely Ibu Pembesar (Superiors Mother) and Perempuan Muda (young woman). ( 2 ) Analysis of impoliteness language in literary works as authentic materials used in the teaching of literature in schools because students can see directly the politeness and impoliteness form of speech